Pineapple Farmers' Perception Of The Influence Of Knowledge, Experience And Motivation On Productivity : PERSEPSI PETANI NANAS MENGENAI PENGARUH PENGETAHUAN, PENGALAMAN DAN MOTIVASI TERHADAP PRODUKTIVITAS - Nasution, Nurjannah; Alfikri; Darnetti; Iryani, Nelvia (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Lareh Sago Halaban Regency, precisely in Nagari Halaban, is one of the areas with the highest pineapple production in Limapuluh Kota Regency, West Sumatra Province. The aim of this research is to analyze the influence of knowledge, experience and motivation on the productivity of Pineapple Farmers in Nagari Halaban simultaneously and partially. The data collection method in this research was to use saturated sampling or census where the entire population, namely 30 pineapple farmers, were sampled using interviews and questionnaires. Data was obtained through a questionnaire and analyzed using the classic assumption test, multiple linear regression. Statistical analysis shows that the relationship between the independent and dependent variables is quite strong (R = 76.9%). Adjusted R Square is 54.5% of the variation in the influence of the independent variable on the dependent variable, while the remaining 45.5% is influenced by other factors not discussed in this research. Based on the F test, the independent variables (knowledge, experience and motivation) have a significant effect on the dependent variable (farmer productivity). The F test shows that overall the independent variables have a significant effect on farmer productivity. The results of the t test state that all independent variables have a positive and significant effect on farmer productivity.